(untitled) (International Conference on Computers in Education, 2013)
Research in ubiquitous learning (U-learning) has gained attention of a large number of researchers and a number of ubiquitous learning systems are now available in the literature. Majority of these systems have been developed to resolve a specific problem in a given context; their development approaches do not dictate ubiquitous context usage requirements to fill in. U-learning systems developers need to have a clear and a general view of how their intended systems make use of the ubiquitous context. This paper introduces a comprehensive view of context usage through three different view-points inspired from Dowson’s work (Dowson, 1993) each one capturing a particular aspect of context handling. Then a set of facets is associated to each given aspect in order to study, understand and appropriately describe it. The findings of this research are aimed to provide context-aware u-learning system developers a clear understanding of the context usage in such systems and help in underlining the requirements of the u-learning environment. This research is also aimed to help in comparing and evaluating context-aware u-learning systems according to the descriptive system views.